Effect of the Prodegradant-Additive Plastics Incorporated on the Polyethylene Recycling - Miguel Aldas; Andrea Paladines; Vladimir Valle; Miguel Pazmiño; Francisco Quiroz (International Journal of Polymer Science)
The effect of degraded plastic with prodegradants on the polyethylene properties was studied. First, the mixture of low-density polyethylene (LDPE) with 5 wt.% prodegradant (oxo-degradable) additive was prepared by melt processing using a mixer chamber. Then, the degradation of the mixtures was evaluated by exposing the oxo-degradable LDPE in a Xenon arc chamber for 300 hours. The degraded material was characterized by infrared spectroscopy (FTIR) assessing the carbonyl index and the hydroperoxide band. Then, different percentages of degraded material (1, 5, 10, 20, and 50 wt.%) were incorporated into the neat LDPE. Mechanical and rheological tests were carried out to evaluate the recycling process of these blends. Also, the feasibility of the blends reprocessing was determined by analysing the melt flow index for each heating process and shear stress applied. It was evidenced that the increment of the content of the degraded material in the neat LDPE decreased the mechanical strength and the processability of blends due to the imminent thermal degradation. All the test results showed that the incorporation of degraded material causes a considerable reduction in the matrix properties during the reprocessing. Nevertheless, at low concentrations, the properties of the oxo-degradable LDPE–LDPE blends were found to be similar to the neat LDPE.